PERBANDINGAN BRAND EQUITY PRODUK SHAMPOO MEREK SUNSILK DENGAN MEREK PANTENE - Raras Aristyani, Ida Ayu; Yasa, Ni Nyoman Kerti (Jurnal Manajemen dan Kewirausahaan, 2013)
The objectives of the study were to know the difference in brand equity and its elements between shampoo products with brand Sunsilk and Pantene. The data analysis technique used was the mean difference test with paired samples. Based on the results of the study, it was found that there is no difference between brand equity Sunsilk with Pantene. the four dimensions of brand equity, just a different one, namely brand perceived quality. Therefore the next shampoo brand Sunsilk should be more focus on the improvement of the quality of its products by way of innovation in flavor, ingredients, and overall quality so as to always be in the top brand position together Pantene.